2012
DOI: 10.7314/apjcp.2012.13.8.4007
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of RIZ1 to Regulation of Proliferation and Migration of a Liver Fluke-Related Cholangiocarcinoma Cell

Abstract: Purpose: Retinoblastoma-interacting zinc finger gene (RIZ1) is a tumor suppressor gene which is highly inactivated by promoter hypermethylation in patients with liver fluke-related cholangiocarcinoma (CCA). Epigenetic aberration of this gene might withdraw the ability to restrain tumor cell proliferation and migration. We aimed to define the role of RIZ1 on cell proliferation and migration in CCA cell line. Materials and methods: Small interference RNA (siRNA) was used to knock down the expression of RIZ1 in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…Reduction of RIZ1 resulted in an increase in tumor cell proliferation and migration. 33 In our previous study, RIZ1 mRNA expression in cervical cancer tissues was significantly lower than that in normal cervical tissues, and RIZ1 expression was absent in cervical cancer SiHa cell line. 32 So we upregulated the expression of RIZ1 in SiHa cells by transfecting pcDNA3.1(+)-RIZ1 plasmid, which significantly reduced cell proliferation, thereby suggesting that upregulation of RIZ1 expression had obvious inhibitory effect on SiHa cell proliferation (Table 2).…”
Section: Discussionmentioning
confidence: 77%
“…Reduction of RIZ1 resulted in an increase in tumor cell proliferation and migration. 33 In our previous study, RIZ1 mRNA expression in cervical cancer tissues was significantly lower than that in normal cervical tissues, and RIZ1 expression was absent in cervical cancer SiHa cell line. 32 So we upregulated the expression of RIZ1 in SiHa cells by transfecting pcDNA3.1(+)-RIZ1 plasmid, which significantly reduced cell proliferation, thereby suggesting that upregulation of RIZ1 expression had obvious inhibitory effect on SiHa cell proliferation (Table 2).…”
Section: Discussionmentioning
confidence: 77%
“…Wen dong et al (28) found that RIZ1 gene is silenced in human esophageal squamous cell carcinoma and it is concentration is down regulated. Finaly Khaenam et al (29) found that (RIZ1) inactivated by promoter hypermethylation in patients with liver fluke-related cholangiocarcinoma (CCA).…”
Section: Discussion:-mentioning
confidence: 99%
“…It is the 2 nd most common malignancy related mortality worldwide with 745,000 deaths per year (2). Its incidence is continuously increasing throughout the world (3)(4)(5). In Egypt, between 1993 and 2002, there was an almost two fold increase in HCC among patients with chronic liver disease (6).…”
Section: …………………………………………………………………………………………………… Introduction:-mentioning
confidence: 99%
See 1 more Smart Citation
“…A case-control study conducted in China also showed that infection with the hepatitis B virus can be a possible risk factor for CCa development [ 4 ]. Patients are usually diagnosed with CCa in the advanced stages of the tumor, which makes it a difficult condition to cure, thus rendering the prognosis very poor [ 5 ]. CCa is resistant to radiation therapy and conventional chemotherapy [ 6 ].…”
Section: Introductionmentioning
confidence: 99%